Interventions for disruptive behaviors reducing problems and building skills - Fabiano, Gregory A. (The Guilford practical intervention in the schools series., 2016)
"Children and adolescents with disruptive behavior disorders struggle both in and outside the classroom. This book gives school practitioners vital tools for supporting students' positive behavior as well as their academic and social success. Chapters review effective behavioral interventions at the whole-class, targeted, and individual levels; parent training programs; and strategies for building adaptive skills. Core evidence-based techniques are illustrated with vivid, concrete examples. Ways to integrate the strategies into a school's multi-tiered model of prevention and intervention are discussed. In a large-size format with lay-flat binding for easy photocopying, the book includes 14 reproducible forms and handouts. Purchasers get access to a Web page where they can download and print the reproducible materials"--Provided by publisher.